Motivational stragegies in physiotherapy to increase adherence & optimise health behaviour change - McGrane, Niall (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2015)
The primary focus of this research was to explore motivational strategies in physiotherapy to improve adherence and elicit health behaviour change. Research has indicated poor adherence to physiotherapy prescriptions and physical activity guidelines. Incontestable epidemiological evidence highlights the fact that healthcare in the 21th Century will be dominated by an escalation in chronic lifestyle-related conditions and healthcare is evolving to reflect this. Healthcare in Ireland, and elsewhere, is changing from a system focused on the treatment of illnesses to one focused on illness prevention and wellbeing. Physiotherapists are well placed to influence health behaviours and can play a leading role in this evolution of healthcare. Research is however required to explore the current situation among members of the physiotherapy profession with regards to improving adherence and eliciting health behaviour change.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin.